2019
DOI: 10.1136/archdischild-2019-317650
|View full text |Cite
|
Sign up to set email alerts
|

Postnatally acquired cytomegalovirus infection in extremely premature infants: how best to manage?

Abstract: Postnatal cytomegalovirus (pCMV) infection is a common viral infection typically occurring within the first months of life. pCMV refers to postnatal acquisition of CMV rather than postnatal manifestations of antenatal or perinatal acquired CMV. pCMV is usually asymptomatic in term infants, but can cause symptomatic disease in preterm (gestational age <32 weeks) and very low birth weight (<1500 g) infants resulting in sepsis, pneumonia, thrombocytopaenia, neutropaenia, hepatitis, colitis and occasionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…reported that microwave irradiation at 500 W for 40 s is a practical method for the prevention of CMV infection via breast milk 5 . Based on this case, we started Holder pasteurization (63 °C for 30 min) of breast milk to completely inactivate CMV for extremely premature infants from mothers in whom CMV infection was not completely excluded, although it may reduce the nutritional, immunological, and endocrinological properties 2 …”
Section: Figmentioning
confidence: 99%
“…reported that microwave irradiation at 500 W for 40 s is a practical method for the prevention of CMV infection via breast milk 5 . Based on this case, we started Holder pasteurization (63 °C for 30 min) of breast milk to completely inactivate CMV for extremely premature infants from mothers in whom CMV infection was not completely excluded, although it may reduce the nutritional, immunological, and endocrinological properties 2 …”
Section: Figmentioning
confidence: 99%
“…In breast milk-acquired pCMV, antiviral therapy in symptomatic infants may be useful in reduction of the severity of symptoms and the duration of illness. 81 Other potential interventions that could be conceived of would include administration of high-titer anti-CMV immune globulin to high-risk infants, or therapeutic vaccination of lactating mothers of VLBW premature infants, toward the goal of augmenting CMV immunity in milk. This approach would require licensure of a CMV vaccine, and elucidation of the aspects of protective immunity that prevent pCMV transmission to VLBW infants.…”
Section: Prevention Effortsmentioning
confidence: 99%
“…Since recent reports have emerged in cCMV that long‐term oral nucleoside therapy improves neurodevelopmental outcomes, the use of these agents may be of considerable therapeutic importance for pCMV infection, if the impact on neurodevelopmental outcomes can be confirmed in future prospective studies. In breast milk‐acquired pCMV, antiviral therapy in symptomatic infants may be useful in reduction of the severity of symptoms and the duration of illness 81 . Other potential interventions that could be conceived of would include administration of high‐titer anti‐CMV immune globulin to high‐risk infants, or therapeutic vaccination of lactating mothers of VLBW premature infants, toward the goal of augmenting CMV immunity in milk.…”
Section: Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…infections is critical, as the long-term complications and treatment recommendations differ significantly. [10][11][12] Proving a congenital CMV infection requires the detection of viral shedding or the presence of viral deoxyribonucleic acid (DNA) in the newborn infant within 3 weeks of birth. 10,11 If CMV is detected later in life, it could be the result of either congenital CMV or postnatal CMV infections.…”
Section: Distinguishing Between Congenital CMV and Postnatal Cmvmentioning
confidence: 99%